Learning and Growth Dimension of the Balanced Scorecard and Its Influence on Cooperative Performance: A Study of Nawalparashi District, Nepal - Upadhyay, Jitendra Prasad; Pokhrel, Pashupati (Journal of Islamic Economics Perspectives, 2024)
The main objective of the study is to analyze the impact of learning and growth dimension on the performance of cooperative in Nepal. The "Learning and Growth" dimension in the “Balanced Scorecard” is crucial because it focuses on the growth and nurturing of human capital, an organization's most valuable asset. This perspective specifically targets the enhancement of employees' abilities, knowledge, and skills, which is essential to a competitive advantage and achieving long-term organizational goals. Due to the specific nature of research objectives, descriptive-cum- causal comparative research design has been used. The findings of the study clearly indicate Learning and Growth dimension with human capital, knowledge capital and institutional capital are very important for increasing the performance of employee in cooperative organization.